The Educational Institution as a Health Facility - Sundararaman, T. (JOURNAL OF INDIAN EDUCATION, 2010)
The child of school going age and the adolescent of college going age represent almost 30 per cent of the population. Of the approximately 19.39 crore children in the elementary education age group about 14.71 crore are enrolled in schools. Including the child attending the preschool the number is nearer 22 crore with an attendance of 15.6 crore. Though there is an unfinished agenda of achieving universal schooling, as access to schools and retention improves, we now need to bring more focus on improving the quality of schooling. The main challenge in quality is educational attainment. There has been increasing concern about the high degree of ‘wastage within schools’ – large numbers of children who pass out from the elementary school without even acquiring fluent literacy or an adequate level of numeracy. This is not only a problem of the elementary school. At every level, the educational system is challenged to ensure that students acquire the knowledge, skills and confidence needed for them to become useful citizens and develop their own lalent abilities and creative potential to the maximum.